One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae: Meconematinae) from Guangxi, China - Chen, Lixuan; Mao, Shaoli; Chang, Yanlin (Zootaxa, 2019)
One new species of the genus Xizicus Gorochov, 1993 is described, namely Xizicus (Eoxizicus) lobicercus sp. nov. from China. In addition, morphological photograph of Xizicus (Eoxizicus) divergrntis (Liu & Zhang, 2000) are provided. All the type specimens are deposited in the Museum of Hebei University.